The influence and mechanism exploration of hydration environment on the stability of natural clay crude oil emulsion - Zhang, Shusong; Liu, Tianyu; Chen, Qingyuan; Xiao, Bao; Xian, Xiaokang; Ye, Zhongbin (Frontiers in Energy Research, 2024)
The study investigated the effects and mechanisms of clay content, emulsion water content, pH, and metal cations on clay-crude oil emulsions. The results indicate the following: 1) At a water content of 50 V/V.%, montmorillonite can form emulsions with crude oil at different concentrations, with the highest stability observed at 5 wt.% content. In contrast, chlorite, illite, and kaolinite cannot form emulsions at low concentrations. 2) Under acidic conditions, montmorillonite, illite, and chlorite cannot form emulsions with crude oil, or the emulsions are highly unstable. However, kaolinite forms more stable emulsions under acidic conditions. In alkaline environments, emulsions formed by all clay minerals exhibit increased stability. 3) The order of the effectiveness of different metal cations in reducing the stability of montmorillonitecrude oil emulsions is K + > Na + > Mg 2+ > Ca 2+ , while for chlorite, illite, and kaolinite, it is Mg 2+ > Ca 2+ > K + > Na + . 4) The factors that influence the stability of clay-crude oil emulsions are the arrangement of clay particles in water and the dispersion capability of clay particles in water. The most significant influencing factor is the arrangement of clay particles in water.